Pengaruh Durasi dan Konsentrasi Pelarut Ekstrak Etanol Daun Teh (Camellia sinensis) Menggunakan Metode Ultrasonik Terhadap Aktivitas Antibakteri Escherichia coli - Thessarah Lia; Ismi rahmawati; Ghani Nurfiana Fadma Sari (CERATA Jurnal Ilmu Farmasi, 2026)
Tea leaves (Camellia sinensis) are one of the plants that contain flavonoids, tannins, alkaloids, and secondary metabolites of catechins that have the potential as antibacterials. Extraction using the Ultrasonic Assisted Extraction (UAE) method is influenced by the duration and concentration of the solvent. The purpose of this study was to determine the effect of different durations and solvent concentrations on the antibacterial activity of Escherichia coli tea extract using the UAE method. Tea leaves were extracted using the UAE method with sonication waves using 50%, 70%, and 96% ethanol solvents with a duration of 15, 30, and 45 minutes, as much as 25 grams in 250 ml. The extract was dissolved in 10% DMSO and an antibacterial activity test was carried out with a concentration of 75% as much as 50 µL per well. The negative control in the bacterial activity test used 10% DMSO, and used ciprofloxacin as a positive control. The antibacterial activity test was determined using the well diffusion method to determine the diameter of the inhibition zone. The test results data were analyzed statistically using SPSS. The results showed that tea leaves have antibacterial activity against Escherichia coli bacteria, the resulting yield related to variations in solvent concentration and extraction duration did not differ significantly, however the results of the inhibition test against Escherichia coli bacteria showed significant differences. Tea leaf extract extracted with UAE with 70% ethanol for 30 minutes had the highest inhibition diameter resulting in antibacterial activity with an average value of 13.475mm ± 0,38.